Highlights in poloxamer-based drug delivery systems as strategy at local application for vaginal infections - Carvalho, Gabriela Corrêa [UNESP]; Araujo, Victor Hugo Sousa [UNESP]; Fonseca-Santos, Bruno; de Araújo, Jennifer Thayanne Cavalcante [UNESP]; de Souza, Maurício Palmeira Chaves [UNESP]; Duarte, Jonatas Lobato [UNESP]; Chorilli, Marlus [UNESP] (Elsevier, 2021)
Infectious diseases related to the vagina include diseases caused by the imbalance of the vaginal flora and by sexually transmitted infections. Some of these present themselves as a public health problem due to the lack of efficient treatment that leads to their complete cure, and others due to the growing resistance to drugs used in therapy. In this sense, new treatment strategies are desirable, with vaginal administration rout being a great choice since can bypass first-pass metabolism and decrease drug interactions and adverse effects. However, it is worth highlighting limitations related to patient's discomfort at application time. Thereby, the use of poloxamer-based drug delivery systems is desirable due its stimuli-sensitive characteristic. Therefore, the present review reports a brief overview of poloxamer properties, biological behavior and advances in poloxamer applications in controlled drug release systems for infectious diseases related to the vagina treatment and prevention.
Keywords: Biological behavior; Drug delivery; Infectious diseases; Poloxamer; Vaginal application